Report of the Second Conference on Transport Studies - Planning Commission (Planning Commission, 1966)
At the invitation of the Joint Technical Group for Transport Planning, Planning Commission, the second Conference on transport studies of the Directors incharge of Regional Transport Survey Units and the associated Railway Officers, was held at New Delhi on 20th and 21st May, 1966. All the States and the Union Territories where these regional transport surveys were being carried out sent representatives to the Conference. Besides the official representatives, some experts from universities, research institutions etc., who were specially invited, participated in the Conference. The names of the participants are given in Appendix.The Conference was presided over by Shri Tarlok Singh, Member incharge of Transport in the Planning Commission. The inaugural speech made by Shri Tarlok Singh is briefly reproduced in Section II. The Conference was also addressed by some members of the Planning Committee for Transport (Secretaries of the Ministries concerned), Director General, National Council of Applied Economic Research, Director, Central Road Research Institute, Director General, Road Development and special invitees. A brief resume of their observations may be seen in Section III of the report.
Planning Commission (Joint Technical Group for Transport Planning)